2019
DOI: 10.3390/genes10090669
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Prediction and Genome-Wide Association Studies of Flour Yield and Alveograph Quality Traits Using Advanced Winter Wheat Breeding Material

Abstract: Use of genetic markers and genomic prediction might improve genetic gain for quality traits in wheat breeding programs. Here, flour yield and Alveograph quality traits were inspected in 635 F6 winter wheat breeding lines from two breeding cycles. Genome-wide association studies revealed single nucleotide polymorphisms (SNPs) on chromosome 5D significantly associated with flour yield, Alveograph P (dough tenacity), and Alveograph W (dough strength). Additionally, SNPs on chromosome 1D were associated with Alveo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 59 publications
8
15
2
Order By: Relevance
“…In contrast, the two alveograph parameters ALVL and ALVPL indicative of dough extensibility and of the balance between dough extensibil-ity and strength, respectively, were more difficult to predict and were also associated with greater MAAPE values (lower prediction accuracy). Similar results were reported in the study of Battenfield et al (2016) and Juliana et al (2019), where the parameter ALVPL was associated with the lowest correlation values, and by Kristensen et al (2019), where ALVL was associated with the lowest predictive ability among the alveograph parameters. Together, the results reported here and in previous studies suggest that dough extensibility, as expressed by the alveograph parameters ALVL and ALVPL, is hard to predict and highly affected by several factors other than genetics.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In contrast, the two alveograph parameters ALVL and ALVPL indicative of dough extensibility and of the balance between dough extensibil-ity and strength, respectively, were more difficult to predict and were also associated with greater MAAPE values (lower prediction accuracy). Similar results were reported in the study of Battenfield et al (2016) and Juliana et al (2019), where the parameter ALVPL was associated with the lowest correlation values, and by Kristensen et al (2019), where ALVL was associated with the lowest predictive ability among the alveograph parameters. Together, the results reported here and in previous studies suggest that dough extensibility, as expressed by the alveograph parameters ALVL and ALVPL, is hard to predict and highly affected by several factors other than genetics.…”
Section: Discussionsupporting
confidence: 88%
“…When analyzing the prediction accuracies associated with each quality trait, we found that the results obtained in the present study exceeded (Battenfield et al, 2016;Kristensen et al, 2019) or were comparable to (Haile et al, 2018;Juliana et al, 2019) the results reported in previous studies.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Perhaps it is no coincidence that the first molecular marker developed for wheat quality was one for a waxy gene, and the research was conducted in Western Australia, where there were ongoing efforts to breed for udon noodle wheats. This work has been developed further by researchers to expand the characterization of this gene and its homologues in wheat and other associated genes for granule-bound starch synthase I (GBSSI) proteins that are responsible for amylose synthesis and the three starch synthase II (SSIIa) enzymes involved in amylopectin synthesis (11,12). Molecular markers for these loci have been used extensively as an efficient approach to both maintain the quality characteristics of the noodle program, as well as facilitate the incorporation of new genetics into the program without large detrimental impacts on noodle quality.…”
Section: Breeding Of Partial Waxy Wheatsmentioning
confidence: 99%